Synthesis and characterization of dried leaves derived carbon quantum dots for metal ions sensing and photocatalytic application - Khor, Jia Min (2018)
In this work, carbon quantum dots (C-dots) was successfully synthesized by hydrothermal treatment using dried leaves as green precursor for metal sensing and photocatalytic degradation of MB dye. Graphitic carbon nitride (g-C3N4) was combined with C-dots to prepare C-dots/g-C3N4 composites with three different weight percentage at 0.6, 0.8 and 1.0 wt%, respectively. The morphological structure, optical properties and chemical compositions of C-dots and composites were characterized using various spectroscopic techniques. C-dots solution portrayed a significant fluorescence property that bright blue-green fluorescence can be observed by naked eye under ultraviolet (UV) light irradiation. The highest fluorescence emission was recorded at 320 nm with the optimal excitation wavelength of 423 nm. Quenching effect of fluorescence C-dots solution was observed in the presence of different metal ions. C-dots is more selective towards Fe3+ compared to other metal ions. The decrease of X-ray Diffraction (XRD) peak intensity at 12.8° and 27.6° indicated the successful incorporation of C-dots into g-C3N4. X-ray photoelectron spectroscopy (XPS) revealed two major peaks of C-C and C-O that mainly contributed by major carbon species in C-dots/g-C3N4 composite. Ultraviolet-visible diffuse reflectance spectroscopy (UV-DRS) results displayed red-shifted adsorption spectra of C-dots/g-C3N4 composites from 500 nm to 800 nm. Meanwhile, C-dots/gC3N4-0.8 exhibited the longest charge carrier lifetime with 4.131 ns from timeresolved fluorescence (TRPL) analysis. No upconvertion photoluminescence (UCPL) was detected in C-dots based on the photoluminescence (PL) study. The loading of C-dots on g-C3N4 reduced the band gap from 2.7 eV to 2.59 eV. The g-C3N4 vii exhibited the best photocatalytic performance (57.52 %) because high adsorption capacity of C-dots/g-C3N4 composites contributed to low degradation efficiency that retarded the re-adsorption of MB dye during the photocatalysis. Among the composites, C-dots/g-C3N4-0.8 exhibited the best photocatalytic performance within 180 minutes of reaction time owing to efficient separation of charge carriers.